2015
DOI: 10.2501/ijmr-2015-007
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Structures of Brand and Country Images, and Their Effects on Product Evaluation

Abstract: Marketers are interested in how consumers perceive product cues in order to build an appropriate marketing mix. Country and brand images are some of the cues proven to be of significant impact on consumer behaviour. This paper studies country and brand image multidimensional structures across several brands, countries and products. A model relating country image to brand image and then to product evaluation was built with country and brand image as multidimensional concepts. A within-subject intercultural inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…The relationship between attitudes and purchase intentions has been examined in different settings and the findings of these researchers indicate that there is a significant positive relationship between attitudes and intentions (Dabholkar and Bagozzi, 2002;Hsu et al, 2017). In line with TRA, prior research into COO effects suggests that COO has a significant influence on consumer product evaluations (Josiassen and Assaf, 2010;Koubaa et al, 2015;Lee et al, 2013;Prentice and Handsjuk, 2016) and purchase decisions (Awada and Yiannaka, 2012;Dobrenova and Terlutter, 2015;Godey et al, 2012). Hence, it is hypothesised that;…”
Section: The Effect Of Consumers' Attitude Towards Products Made In Fmentioning
confidence: 82%
See 1 more Smart Citation
“…The relationship between attitudes and purchase intentions has been examined in different settings and the findings of these researchers indicate that there is a significant positive relationship between attitudes and intentions (Dabholkar and Bagozzi, 2002;Hsu et al, 2017). In line with TRA, prior research into COO effects suggests that COO has a significant influence on consumer product evaluations (Josiassen and Assaf, 2010;Koubaa et al, 2015;Lee et al, 2013;Prentice and Handsjuk, 2016) and purchase decisions (Awada and Yiannaka, 2012;Dobrenova and Terlutter, 2015;Godey et al, 2012). Hence, it is hypothesised that;…”
Section: The Effect Of Consumers' Attitude Towards Products Made In Fmentioning
confidence: 82%
“…As an extrinsic cue that influences consumer product evaluations, COO has the ability to influence consumer product quality perceptions by; (a) activating concepts and knowledge that influence consumer evaluation of other product cues; (b) inferring the quality of the product as a heuristic or a cognitive shortcut without considering other attribute information; (c) depicting a product attribute in a similar manner to other specific product attributes; and (d) attracting consumer attention to COO rather than to other attribute information (Hong and Wyer, 1989). Prior research indicates that COO has a significant influence on consumers' product evaluations (Costa et al, 2016;Josiassen and Assaf, 2010;Koubaa et al, 2015) and purchase decisions (Awada and Yiannaka, 2012;Dobrenova and Terlutter, 2015;Godey et al, 2012). These studies have been conducted in a variety of contexts focusing on different consumer segments (Bhaskran and Sukumaran, 2007;Roth and Diamantopoulos, 2009).…”
Section: Country Of Origin (Coo) Effectsmentioning
confidence: 99%
“…De Nisco et al (2015) state that in PCI literature, country image is often operationalized through the following three components (see also Laroche et al, 2005;Papadopoulos, 1993;Papadopoulos et al, 2013;Li et al, 2014;Koubaa, Methamem, & Fort, 2015 Despite the theoretical appeal of the above conceptualization, most studies using the PCI approach have not considered the multidimensionality of country image when operationalizing the construct (Laroche et al, 2005;Koubaa et al, 2015). For example, according to Li et al (2015), most studies consider country image as a cognitive construct (see also Elliot, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, Laroche et al (2005) tested a model of multidimensional country image and found that country image is a three-dimensional construct consisting of cognitive, affective, and conative components. Also Koubaa et al (2015) found that country image has a multidimensional rather than a single-factor structure.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite fifty years' study of country-of-origin (COO) effects (see Chen et al 2014;Al-Aali et al 2015;Arora et al 2016), findings are contradictory, empirically incongruous and theoretically weak. While consensus has been reached regarding the CAN elements (see Koubaa, Methamem 2015), few empirical studies simultaneously apply these facets of consumer-preference formation; even then they "fail to sufficiently implement this distinction (of country image) at the operationalization stage" (see Roth, Diamantopoulos 2009: 736). Also, while implied that foreign purchase behaviors (FPB) and domestic purchase behaviors (DPB) are culture bound, there is limited integration of cultural elements into COO and/or ethnocentrism models.…”
Section: Introductionmentioning
confidence: 99%